Echocardiography from a transhepatic approach in left ventricular assist device patients with difficult transthoracic imaging. Issue 4 (21st April 2021) - Strachinaru, Mihai; Hirsch, Alexander; Bowen, Daniel; Caliskan, Kadir
Abstract: Background: Left ventricular assist devices (LVADs) are increasingly used in the treatment of end-stage heart failure. One important limitation in the follow-up of these patients is the very difficult echocardiographic image, because of the interposition of implanted materials. Case summary : We present here a case series of LVAD patients with severely limited transthoracic echocardiographic windows in whom the echocardiographic analysis of the left and right ventricular function could be obtained from a very unusual approach, using a right intercostal transhepatic window, allowing visualization of the heart chambers and quantification of function even in these very challenging cases. In one case, the result was confirmed by computed tomography. In the second case, computed tomography images were unreliable because of strong artefacts from the LVAD system and implantable cardioverter-defibrillator leads, but the transhepatic approach still provided sufficient image quality in order to allow the imaging follow-up of the patient. In the third case, the transhepatic window was the only approach that provided echocardiographic images, and due to the good visualization of the heart cavities, this imaging technique was considered sufficient for follow-up studies in this stable subject with LVAD as destination therapy. Discussion : The transhepatic window may represent a good alternative in selected LVAD patients with very difficult acoustic access in traditional transthoracic views. Modified or alternate echocardiographic windows may reduce the need for invasive procedures (transoesophageal echocardiography) or imaging methods using radiations.